FRI0496 Long Term Safety and Efficacy of Anakinra in Adult Patients with Refractory Recurrent Idiopathic Pericarditis. (15th July 2016) - Antonatou, K.; Vasileiou, P.; Koutsianas, C.; Lazaros, G.; Vassilopoulos, D.
Abstract : Background: Our previous open label study has shown that IL-1 inhibition with anakinra was an efficacious, safe and steroid-sparing agent for the short term treatment of refractory recurrent idiopathic pericarditis in adults. However long term data are not available in such patients. Objectives: The aim of this study, which is a follow-up of the initial cohort of patients, was to assess the long term safety and efficacy of Anakinra in adult patients with refractory recurrent idiopathic pericarditis. Methods: Eleven patients with treatment-resistant idiopathic recurrent pericarditis were included (a new patient was added to the initial cohort of 10 patients). All patients were resistant and/or intolerant to previous treatment with aspirin and/or NSAIDs, colchicine and corticosteroids (CS) while two (18%) had failed azathioprine therapy. Initially all were treated with daily subcutaneous injections of Anakinra (100 mg) with gradual tapering of the administered dose (daily for 6 months, followed by every other day for 6 months). Recurrences as well as adverse events were recorded in all patients. Results: Among the 11 patient included there were 6 males with a mean age of 42 ± 16.8 years and a median disease duration of 37 months. Patients had a median of 8 recurrences prior to Anakinra initiation and were CS-resistant (mean daily prednisolone dose at baseline: 14.7 ± 7.6 mg). Patients were followed for a period of approximately 3 years (median follow-up time: 35 months). All patients responded initially to Anakinra and all were able to discontinue CS rapidly (median time to discontinuation: 6 weeks). During the long term, follow-up, 3 patients discontinued anakinra (27.5%) and remain free of recurrences without any treatment ever since. Five patients (45%) remain on a reduced dose of Anakinra (once a week n=1, twice a week n=1, three days a week n=1, four days a week n=2). Most recurrences occurred while the dose of Anakinra was reduced from three to two injections per week (mean number of recurrences: 2.2 ± 1.4). Three patients continue on full dose Anakinra (one had started therapy 3 months ago). None of these patients had restarted CS. No significant side effects were seen during the long term follow up of these patients and no patient discontinued therapy due to side effects. Conclusions: During long term follow-up, Anakinra remains a highly efficacious and safe medication for the treatment of refractory recurrent idiopathic pericarditis in adults. All patients remain CS-free and more than a quarter (27.5%) of them were able to discontinue all therapies. Approximately half remain on a reduced dose Anakinra with excellent disease control. Acknowledgement: Supported by research grants from the Special Account for Research Grants (S.A.R.G.), National and Kapodistrian University of Athens, Athens, Greece. Disclosure of Interest: None declared